Human papillomavirus infection is principally found with cervical intra-epithelial neoplasia-III in Toluca, State of Mexico - Hugo Mendieta-Zerón; Raúl de León-Escobedo (Elsevier, 2009)
Summary: Introduction: To describe the prevalence of human papillomavirus infection (HPV) in cases of cervical intra-epithelial neoplasia (CIN), micro-invasive carcinoma and invasive carcinoma in Toluca, State of Mexico. Materials and methods: Cross-sectional study analysing slides with the diagnosis of CIN I to invasive carcinoma for one year and reporting the presence of HPV; also identifying these cervical-uterine cancer stages noted during one semester in the registery of histopathological studies, at the Department of Pathology, General Regional Hospital 220, Instituto Mexicano del Seguro Social (IMSS). Results: In one year, from a total of 5755 studies, 731 (13%) were of cervical-uterine cancer, 112 (16%) of these were positive for some stage of cervical cancer and 46.43% had HPV infection. In one semester, 2918 histopathological studies were done, 341 (11.68%) of these were cervix uterine biopsies, colposcopies and hysterectomies. 62 women (18.18%) diagnosed with CIN II-III, carcinoma in situ (CIS), micro-invasive carcinoma or invasive carcinoma and finding HPV infection in 51.92% of total cases. Conclusions: The prevalence of HPV was higher than that reported in developed world and CIN II-III are the most common stages in Toluca, State of Mexico. Keywords: Cervical intra-epithelial neoplasia, Cervical-uterine cancer, Detection, Human papillomavirus